Practical synthetic organic chemistry : reactions, principles, and techniques - Caron, Stephane (Hoboken, NJ : Wiley, 2019)
"This book is a hands-on guide for the organic chemist. Focusing on the most reliable and useful reactions, the chapter authors provide the information necessary for a chemist to strategically plan a synthesis, as well as repeat the procedures in the laboratory. Towards this purpose, the reaction chapters offer information on the basics of the reaction, the synthetic procedure(s), mechanism, and scope of the reaction. Later chapters discuss information that is not common knowledge outside of process chemistry groups like practical solvents and green chemistry concepts. The new edition adds content on recent advances in CH activation, photoredox and electrochemistry, continuous chemistry, and application of biocatalysis in synthesis. Together, these make the book a valuable desktop reference for professionals working in and students studying organic chemistry or related fields"--
Aliphatic nucleophilic substitution -- Addition to carbon-heteroatom multiple bonds -- Addition to carbon-carbon multiple bonds -- Nucleophilic aromatic substitution -- Electrophilic aromatic substitution -- Selected catalytic reactions -- Rearrangements -- Eliminations -- Reductions -- Oxidations -- Selected free radical reactions -- Synthesis of "nucleophilic" organometallic reagents -- Synthesis of common aromatic heterocycles -- Access to chirality -- Biocatalysis -- Green chemistry -- Continuous chemistry -- General solvent properties -- Practical chemistry concepts: tips for the practicing chemist or things they don't teach you in school.
Includes bibliographical references and index.
Keywords: Organic compounds -- Synthesis